Pengaruh Lama Waktu Biofermentasi Chromolaena Odorata dengan Sumber Karbon Gula Lontar Cair terhadap Kandungan NDF, ADF Serta Mineral Ca dan P - Tsael, Yulvi Lidia; Lestari, Gusti A. Y.; Oematan, Gustaf; Benu, Imanuel (Animal Agricultura, 2024)
The purpose of this study was to determine the effect of the length of biofermentation time of Chromolaena odorata with the best source of liquid palm sugar carbon to obtain the content of NDF, ADF, and Minerals Ca and P. The method used in this study was an experimental method with Complete Randomized Design (RAL) with 4 treatments and 4 repeats so that there were 16 experimental units. The treatment levels are as follows: LB21 = Biofermentation duration for 21 days (as control), LB14 = Biofermentation duration for 14 days, LB7 = Biofermentation duration for 7 days, LB0 = Biofermentation duration for 0 days. The variables studied were NDF, ADF, and Ca and Phosphorus Minerals. The results of the study are as follows: LB21: NDF of 40.286%, ADF of 29.2775%, Calcium of 0.9105%, Phosphorus of 0.53652%; LB14: NDF of 57.382%, ADF of 36.1975%, Calcium of 0.90725%, Phosphorus of 0.53775%; LB7: NDF of 47.02%, ADF of 30.1275%, Calcium of 0.86925%, Phosphorus of 0.51225%; LB0: NDF of 2.478%, ADF of 40.7375%, Calcium of 0.8045%, Phosphorus of 0.48375%. The results of statistical analysis showed that the long treatment of biofermentation time with a source of liquid palm sugar carbon had a significant effect (P<0,05) to contet ndf dan adf chromolaena odorata, whereas parameter calcium and phosphorus no real effect (P>0.05). It was concluded that the length of biofermentation time of Chromolaena odorata with a source of liquid palm sugar carbon affected the levels of Neutral Detergent Fiber and Acid Detergent Fiber but did not affect the content of Calcium and Phosphorus Minerals.